Knowledge, attitude and practice towards water, sanitation and hygiene among street food vendors in Serdang, Selangor - Abdul Aziz, Nur Al Amin; Mohd Sham, Shaharuddin (Environmental and Occupational Health Society, 2021)
Objective: This study was conducted to determine the level of knowledge, attitude and practice (KAP) towards water, sanitation and hygiene (WASH) among Serdang's street food vendors and determine the KAP level association with sociodemographic characteristics and the food handling course attendance. Method: A pre-tested questionnaire adapted from United Nations Human Settlement Programme containing open ended question and 5-score Likert scale was used and distributed to 85 street food vendors in Serdang, Selangor. Results: The highest frequency (percentage) of Serdang street food vendors, were vendors around age 18-35 years old, 61 (71.8%), male, 55 (64.7%), local 77 (90.6%) and had completed secondary education 45 (52.9%). The mean percentage of score (SD) obtained for knowledge was 76.4% (n=14), attitude 84.4% (n=15), and practice 96.6% (n=13). Out of 85 respondents, 82 (96.5%) had good knowledge, 83 (97.6%) had good attitude, and 84 (98.8%) had good practice towards WASH. Furthermore, Chi-square analysis found an association between citizenship and level of knowledge. There was no association between food handling course attendance with the level of knowledge, attitude and practice. Conclusion: Majority of street food vendors had scored good level of knowledge, attitude and practice towards WASH. However, they can further improve their current knowledge, attitude and practice towards WASH from help of the government in providing better education and more facilities towards the goal of clean water and sanitation. In doing so would help in reducing the prevalence of food and water-related diseases cases in our country.